1993
DOI: 10.1111/j.1399-3054.1993.tb01763.x
|View full text |Cite
|
Sign up to set email alerts
|

On the participation of chloride in bicarbonate‐induced reversal of anion inhibition of photosystem II electron transport in spinach thylakoids

Abstract: Inhibition of electron transport through photosystem II (PS II) by formate (HCO−2) or nitrite (NO−2) in the presence or absence of chloride ions was studied. The inhibition induced by HCO−2 or NO−2 is overcome by HCO−3 more in the presence, than in the absence of Cl−. The data on electron transport are supported by chlorophyll a fluorescence measurements. In experiments. In experiments in which water oxidation was blocked. Cl− was found to facilitate electron transport between bound quinone A (Q−A) and the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Rates obtained in heat-treated thylakoid membranes were 3-5% of control values suggesting that the OEC was almost completely inactivated in heat-treated thylakoid membranes. Effects of anion were observed equally well in heat-shocked thylakoids that are known to have lost the ability to evolve oxygen and so the action of anions was suggested to be on the acceptor side of PS II (Jajoo and Bharti 1993b). However in case of oxalate, inhibition of PS II activity was not observed in DPC ?…”
Section: Effects Of Oxalate On Ps IImentioning
confidence: 94%
“…Rates obtained in heat-treated thylakoid membranes were 3-5% of control values suggesting that the OEC was almost completely inactivated in heat-treated thylakoid membranes. Effects of anion were observed equally well in heat-shocked thylakoids that are known to have lost the ability to evolve oxygen and so the action of anions was suggested to be on the acceptor side of PS II (Jajoo and Bharti 1993b). However in case of oxalate, inhibition of PS II activity was not observed in DPC ?…”
Section: Effects Of Oxalate On Ps IImentioning
confidence: 94%
“…The order of effectiveness of various anions in substituting for Clwas Br -> I -> F -> NO 2 -~ PO 4 3-> HCO 3 -. In our earlier work (Jajoo and Bharti 1993), besides the water oxidation site, Clwas suggested to have a site of action between Q A and Q B . Vliet and Rutherford (1996) observed distinct Cl --depletion effects in PS2 observed under two different Cl --depletion treatments indicating the presence of two distinct binding sites in PS2.…”
mentioning
confidence: 92%
“…It has been reported earlier that the inhibition induced by formate or nitrite can be overcome by bicarbonate (Stemler and Murphy 1985, van Rensen et al 1999). Further, Jajoo and Bharti (1993) showed that the presence of chloride lowers the amount of bicarbonate required to overcome the inhibition induced by nitrite or formate. Loss of S 2 state multiline signal (Jajoo et al 2005) and changes observed in the thermoluminescence studies (Sahay et al 2006b) in nitrite‐treated samples have shown that nitrite probably acts on the donor side of PS II.…”
Section: Introductionmentioning
confidence: 99%